We love the seashore - Tym, Kate.; Christy, Jana (Laguna Hills, CA : QEB Pub., 2007)
On a beautiful day when Dad does not have to go to work, a family goes to the beach for games, swimming, a picnic, a visit to an amusement park, and more. Includes recipes and activities.
Keywords: Family life -- Fiction; Seashore -- Fiction; Amusement parks -- Fiction; Stories in rhyme